Recurrence Rates of Intraosseous Ameloblastoma Cases With Conservative or Aggressive Treatment: A Systematic Review and Meta-Analysis - Qiao, Xue; Shi, Junxiu; Liu, Jiayi; Liu, Jinwen; Guo, Yan; Zhong, Ming (Frontiers in Oncology, 2021)
ABSTRACT Objective This study aimed to systematically investigate and compare the post-treatment recurrence of intraosseous ameloblastoma in patients treated with conservative or aggressive approaches. Methods Systemic searches of PubMed, Medline, Cochrane Library, and Embase databases from inception to October 28, 2020, were conducted. Studies that aimed to evaluate the recurrence of intraosseous ameloblastoma by conservative and aggressive treatment approaches were included. Results A total of 20 studies with 942 ameloblastoma cases were included. Fourteen studies included patients with ameloblastoma who received conservative treatment, and 16 studies reported the overall recurrence rate for patients undergoing aggressive treatment. The pooled results indicated that the recurrence rate for aggressive treatment [0.12, 95% confidence interval (CI) = 0.09–0.16] was significantly lower than that for conservative treatment, with a recurrence rate of 0.30 (95% CI = 0.23–0.39). Similar results were obtained when stratifying the participants by the histological classification. When trying stratification analysis following the original included studies, multicystic ameloblastoma presented a much higher recurrence rate than solid and unicystic ameloblastomas. Conclusion These findings supported the hypothesis that aggressive treatment might lead to a lower recurrence rate than conservative treatment. More studies and meta-analyses following the new histological classification of ameloblastomas are needed to validate and support the findings.